2014
DOI: 10.4236/as.2014.54037
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Heat Waves and Their Impacts on Summer Crop Development in Southern Brazil

Abstract: Periods in the soybean summer cycle that are sensitive to the occurrence of high temperatures were studied. An analysis was performed on the variability of soybean yields associated with crop canopy temperatures during key development periods. A land surface temperature (LST) data series from MODIS (Moderate Resolution Imaging Spectroradiometer) on the Aqua satellite was processed between 2003 and 2012 that covered the entire state of Rio Grande do Sul, in Brazil. Enhanced vegetation index (EVI) data from MODI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
1
5
0
1
Order By: Relevance
“…Several studies applied to Brazil established a relationship between the occurrence of periods marked by high temperatures (often accompanied by high air pollution levels) and an increase in deaths related to cardiovascular/cerebrovascular accidents and respiratory diseases (Gouveia et al, ; Hajat et al, ; Bell et al, ). From an economic point of view, some studies show that the occurrence of exceptionally high temperatures in Brazil can be related to shortages in agriculture and animal production (Gusso et al, ; McKechnie and Wolf, ; Olesen et al, ) and increases in energy consumption due to air conditioning demand. All these socio‐economic impacts are particularly relevant in vast countries like Brazil that present a wide range of ecoregions, a large and diverse population and with several economic sectors heavily weather dependent (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies applied to Brazil established a relationship between the occurrence of periods marked by high temperatures (often accompanied by high air pollution levels) and an increase in deaths related to cardiovascular/cerebrovascular accidents and respiratory diseases (Gouveia et al, ; Hajat et al, ; Bell et al, ). From an economic point of view, some studies show that the occurrence of exceptionally high temperatures in Brazil can be related to shortages in agriculture and animal production (Gusso et al, ; McKechnie and Wolf, ; Olesen et al, ) and increases in energy consumption due to air conditioning demand. All these socio‐economic impacts are particularly relevant in vast countries like Brazil that present a wide range of ecoregions, a large and diverse population and with several economic sectors heavily weather dependent (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, the importance of spectral vegetation indices such as NDVI and EVI, as indicator of crop performance is well documented in literature. For instance, Gusso et al, (2014) found good correlation between EVI and crop yield in Brazil while Kogan et al, (2012) concluded that NDVI is a cumulative indicator of crop growth in Kansas, USA. These observations from other researchers confirm the relative importance of satellite derived vegetation related products in delineating yam growing environment observed in this study.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Optimal canopy-LST values between 298 K (25°C) and 309 K (35°C), with values nearby 303 K (30°C) are most frequently considered the ideal conditions for soybean development (Schlenker & Roberts, 2009). Through a different ecosystem than MT, an important contribution regarding this research is given by Gusso et al (2014) when studying the southern region of Brazil. Those studies observed that slightly warmer than the optimal conditions for growth can potentially increase drought effects (if any) and yield loss, by overheating the vegetation canopy and intensifying plant damage.…”
Section: Correlation Between Lst and Yieldmentioning
confidence: 99%
“…(4) By combining the two LST composites of 16 days (DOY 001-017) as a function of the maximum EVI, we obtain a 32-day composite of canopy-LST when crop canopy vegetation is its maximum. This is an important step because the high incidence of cloud cover exerts a confusing factor during key periods of the vegetation profile (DOY 353 to 033) in MT (Gusso et al, 2014(Gusso et al, , 2017. Additionally, in order to overcome the cloud cover and cloud shadows challenge, the 8-day product (MYD11A2) was combined into a maximum LST of 16 days.…”
Section: Classification Proceduresmentioning
confidence: 99%